Deafness of two geniuses. Beethoven and Goya: Similar lives? (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
We present a brief summary of the lives of Beethoven and Goya from his childhood until his death. Musician and painter succeed in the societies of Vienna and Madrid. Both suffer profound hearing loss. We present original opinions on the etiology of deafness of the two main characters. Similarities in their lives, work and personality are related. In many aspects, they have similar lives: they are contemporary, innovative in his art, both suffer syphilis, they have a tough character and, in both deafness powerfully influences his artistic creation.
Keywords: Deafness, syphilis, innovation, music, painting.